1994
DOI: 10.1111/j.1365-2621.1994.tb02095.x
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer phenomena during osmotic dehydration of apple I. Fresh plant tissue

Abstract: Mass transfer phenomena were qualitatively investigated during osmotic dehydration of fresh apple in concentrated solutions using response-surface methodology. The influence of the main process variables (solute concentration, solute molecular weight, temperature and processing time) were thus determined. Osmotic phenomena, such as plant cell plasmolysis, only had a marked effect on dehydration at moderate temperatures (T < 50°C) and when low molecular weight solutes that could easily penetrate tissues were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 17 publications
6
44
0
9
Order By: Relevance
“…During the process, the water present in the tissues is removed to the solution and mass is transferred between the solution and tissue components. Results obtained by Saurel et al (1994a) indicate that the gradient of osmotic pressure created between the osmotic solution and the vacuolar sap of the fresh material subjected to dehydration is the major driving force of the process at low temperatures and short processing times (under 50°C and up to 30 min for apples). Water and substances from the sap are transported through the semipermeable cell membrane of the biological material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the process, the water present in the tissues is removed to the solution and mass is transferred between the solution and tissue components. Results obtained by Saurel et al (1994a) indicate that the gradient of osmotic pressure created between the osmotic solution and the vacuolar sap of the fresh material subjected to dehydration is the major driving force of the process at low temperatures and short processing times (under 50°C and up to 30 min for apples). Water and substances from the sap are transported through the semipermeable cell membrane of the biological material.…”
Section: Introductionmentioning
confidence: 99%
“…The state of the membrane may change from partial to full permeability, which depends on the process conditions (Torreggiani and Bertolo 2001). According to Saurel et al (1994a), at higher temperatures and long process times transfers are controlled by diffusion phenomena. Thus, inadequate dehydration parameters may lead to unfavorable changes in the dehydrated material, including the loss of semipermeability of cell membranes and substantial losses of valuable nutrients (Chiralt and Talens 2005;Falade and Igbeka 2007) as well as high sugar impregnation, which increases the caloric value of the product.…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings, the mass transfer and final OD product quality depend on several factors, such as: tissue properties (SAUREL et al, 1994;RAOULT-WACK, 1994;KOWALSKA;LENART, 2001); ripeness level in the case of fruits (CHIRALT; FITO, 2003); process temperature (BERISTAIN et al, 1990;HENG;CUQ, 1990); type of solute employed (HENG; GUILBERT; CUQ, 1990;VIAL;CUQ, 1991); syrup concentration (HENG; GUILBERT; CUQ, 1990;PARK et al, 2002, FERNANDES et al, 2006; format and dimension of the fruit pieces (LERICI et al, 1985;PANAGIOTOU;KARATHANOS;MAROULIS, 1998); process time (VIDEV et al, 1990;ARAUJO, 2005) and syrup:fruit mass ratio (LERICI et al, 1985). A few studies also reported on the influence of solution agitation (AZUARA; GARCIA; BERISTAIN, 1996; SAHARI; SOUTI; EMAM-JOMEH, 2006) and the application of vacuum (SHI; CHIRALT, 1995).…”
Section: Experimental Testsmentioning
confidence: 99%
“…(SAUREL et al, 1994;PEREIRA et al, 2006), the reason for such a phenomenon can be the change -due to the temperature rise -in the cell membrane permeability of the vegetable tissue leading to a gradual increase in solids absorption. For the sugar models, a minor negative influence of concentration was also noticed, i.e., greater concentration values contributed to reducing the increase in solids content of the fruit.…”
Section: Multiple Regression Analysesmentioning
confidence: 99%
“…The medlars pieces are traditionally preserved using the candying by dipping in solution of sugar concentrated. The candying facilitates the penetration of solids into fruits and limits the loss in water, whereas the osmotic dehydration facilitates the loss in water and limits the gain of solids [1]. The osmotic dehydration method is widely used for the elimination of the water of the fruit, to obtain a product of intermediate humidity, or as a pretreatment before an additional process such as freezing, freeze-drying, vacuum drying or air drying [2,3].…”
Section: Introductionmentioning
confidence: 99%